Three-dimensional intact-tissue sequencing of single-cell transcriptional states - Wang, Xiao; Allen, William E; Wright, Matthew A; Sylwestrak, Emily L; Samusik, Nikolay; Vesuna, Sam; Evans, Kathryn; Liu, Cindy; Ramakrishnan, Charu; Liu, Jia; Nolan, Garry P; Bava, Felice-Alessio; et al. (Science (American Association for the Advancement of Science), 2018)
Retrieving high-content gene-expression information while retaining three-dimensional (3D) positional anatomy at cellular resolution has been difficult, limiting integrative understanding of structure and function in complex biological tissues. We developed and applied a technology for 3D intact-tissue RNA sequencing, termed STARmap (spatially-resolved transcript amplicon readout mapping), which integrates hydrogel-tissue chemistry, targeted signal amplification, and in situ sequencing. The capabilities of STARmap were tested by mapping 160 to 1020 genes simultaneously in sections of mouse brain at single-cell resolution with high efficiency, accuracy, and reproducibility. Moving to thick tissue blocks, we observed a molecularly defined gradient distribution of excitatory-neuron subtypes across cubic millimeter-scale volumes (>30,000 cells) and a short-range 3D self-clustering in many inhibitory-neuron subtypes that could be identified and described with 3D STARmap.